Effectiveness of Emotional Demonstration Counseling on Knowledge, Attitudes and Behavior of Mothers of Stunting Toddlers in Sukaresmi Village - Tania Fidzikri, Nanda Berliana; Ulfa, Laila; Sulistyowati, Yeny; Zaelani, Ahmad; Syafriyanti, Willyana (Rifa'Institute, 2025)
Introduction: Stunting among toddlers is a pressing concern associated with increased mortality and morbidity risks. Sukabumi Regency in West Java has the second-highest stunting prevalence rate at 37.6% in 2020, as reported by the West Java Health Office. In 2022, Sukaresmi Village, Cisaat District, was identified with the highest stunting prevalence at 20.2%. Objective: This study aims to evaluate the effectiveness of counseling, employing the emotional demonstration method, on knowledge, attitudes, and behaviors of mothers with stunted toddlers in Cisaat Public Health Center's jurisdiction. Method: This research uses a quantitative approach with a pre-experimental pre-post-test design, involving 60 mothers with stunted toddlers. Result and Discussion: The study shows significant positive changes in knowledge, attitudes, and behaviors among mothers who received counseling using the emo-demo method, lecture method, or a combination, as indicated by a p-value of <0.05. Notably, the combined emo-demo and lecture method outperforms either method individually. Conclusion: Based on these results, it is recommended that Cisaat Public Health Center implements health counseling using the emo-demo method combined with lectures, using tailored materials for target groups in stunting prevention. Future research should explore alternative methodologies and larger sample sizes to enhance findings' validity and generalizability in this crucial public health domain